Transformation towards Human Resource Information Systems - Anitha, J.; Aruna, M. (Journal of Management and Development Studies, 2015)
This paper has explored the various factors namely technological factors, organisational factors, environmental factors and psychological factors that influence in the adoption of Human Resource Information Systems (HRIS). The purpose of the paper is to focus on the factors essential for the adaptability and capability of companies to accept the introduction of information systems like HRIS. The paper is descriptive in nature and the respondents are the users of HRIS in small, medium and large scale companies. The users are the employees, managers and executives of the information technology sector. The techniques of descriptive statistics, one way ANOVA, correlation, and linear regression are used in the analysis to measure the existing level of the influential factors of HRIS. The environmental factor is found to have a profound influence on the adoption of HRIS. This implies that the competitiveness and external pressure are the vital forces for the company to sustain in the global environment and in adopting new technologies. As, this paper has focused only on the respondents from the information technology sector,it can be extended to manufacturing and automobile sectors for a comprehensive model development. The model developed can be considered as a main tool for an organisation for introducing new information systems like HRIS. This also encompasses specific components for successful adoption of HRIS.